2021
DOI: 10.1038/s41388-021-01801-w
|View full text |Cite
|
Sign up to set email alerts
|

ST6Gal1 targets the ectodomain of ErbB2 in a site-specific manner and regulates gastric cancer cell sensitivity to trastuzumab

Abstract: The clinical performance of the therapeutic monoclonal antibody trastuzumab in the treatment of ErbB2-positive unresectable gastric cancer (GC) is severely hampered by the emergence of molecular resistance. Trastuzumab’s target epitope is localized within the extracellular domain of the oncogenic cell surface receptor tyrosine kinase (RTK) ErbB2, which is known to undergo extensive N-linked glycosylation. However, the site-specific glycan repertoire of ErbB2, as well as the detailed molecular mechanisms throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
(57 reference statements)
4
31
0
Order By: Relevance
“…Furthermore, high expression of ST6GAL1 in CSCs could eventually promote chemo-resistance (137). Indeed, ST6Gal1 has been linked to resistance to a number of agents including gemcitabine (138), cisplatin (139), trastuzumab (140,141) or gefitinib (142), latter of which appears to involve sialylation and activation of EGFR (142).…”
Section: St6gal1mentioning
confidence: 99%
“…Furthermore, high expression of ST6GAL1 in CSCs could eventually promote chemo-resistance (137). Indeed, ST6Gal1 has been linked to resistance to a number of agents including gemcitabine (138), cisplatin (139), trastuzumab (140,141) or gefitinib (142), latter of which appears to involve sialylation and activation of EGFR (142).…”
Section: St6gal1mentioning
confidence: 99%
“…Our studies support this concept, and furthermore indicate that ST6Gal1 in BCP-ALL is neither an oncogene nor a tumor suppressor. This does not exclude an important contribution of ST6Gal1 to the outcome of specific therapies such as those making use of monoclonal antibodies, as described for the EGFR and ErbB2 (59,60). However, detailed analytical glycan studies of sialylation on CD19, CD22, or CD20 glycoproteins before and after treatment with antibodies or CAR Tcells would be needed to determine if ST6Gal1 N-linked a2,6 sialylation is a contributing factor to resistance in B-cell malignancies treated with such immune therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these works found that sialylation of receptors by ST6GAL1 alters their signaling properties ( 8 , 42 , 43 ). In recent work, sialylation by ST6GAL1 of the oncogenic receptor Erb2 was found to mask the epitope of an anticancer antibody, promoting resistance to treatment ( 45 ). Our data reveal the upregulation of ST6GAL1 expression and α-2,6-sialylation in cancerous ducts.…”
Section: Discussionmentioning
confidence: 99%